Effects of Magnetic Fields in Arc Welding, Laser Welding, and Resistance Spot Welding: A Review. Issue 5 (2nd March 2023) - Xu, Tao; Shi, Yonghua; Cui, Yanxin; Liang, Zhuoyong
Abstract : The pictures show the effect of magnetic fields in different directions, including welding direction, transverse, longitudinal and cusp magnetic fields, on the shape of welding arc and molten pool. The magnetic field can significantly affect the arc morphology and droplet transfer, as well as the macro morphology and microstructure of the weld bead. Further information can be found in the article, number 2200682 by Yonghua Shi, and co‐workers.